Influence of teaching methods on competence of fashion and design students - Mark, Henry (International Journal of Fashion and Design, 2021)
Purpose: The purpose of this research was to assess the influence of teaching methods on competence of fashion and design students. Methodology: A qualitative textual evaluation method was used in this research. Textual analysis consists of review and interpretation of scripts and articles and their inferential context. The research involved literature search and paper review of information on silk fashion growth. The study adopted a desktop literature review method (desk study). Results: The study recognized poor students approach to learning creativity; specifically, the non-application of analytical, conceptual and synthesiscal skills in solving problems. It is expedient to re-iterate that tutors are foremost in the education sector and they make the most difference in knowledge acquisition. Tutors should therefore continuously improve on their professional knowledge and practice by exploring creative applications and nurturing students' creativity at every opportunity. It is widely believed that tutors who vary their instruction possess more professional expertise and produce more learning in their students than do tutors who use the same approach to meet all their learning goals. Unique contribution to theory, practice and policy: The study recommend that lecturers should not solely direct their teaching towards attainment of good examination results. Student should be assisted by their lecturers to take up work placements relevant to their programmes of study to enable them to acquire additional competency skills from experts in the industry.